Abundance of Discoasters during the PETM at Bass River, Wilson Lake and South Dover Bridge - Bralower, Timothy J; Self-Trail, Jean (Supplement to: Bralower, TJ; Self-Trail, J (2016): Nannoplankton malformation during the Paleocene-Eocene Thermal Maximum and its paleoecological and paleoceangraphic significance. Paleoceanography, 31, https://doi.org/10.1002/2016PA002980, 2016)
The Paleocene-Eocene Thermal Maximum (PETM) is characterized by a transient group of nannoplankton, belonging to the genus Discoaster. Our investigation of expanded shelf sections provides unprecedented detail of the morphology and phylogeny of the transient Discoaster during the PETM and their relationship with environmental change. We observe a much larger range of morphological variation than previously documented suggesting that the taxa belonged to a plexus of highly gradational morphotypes rather than individual species. We propose that the plexus represents malformed ecophenotypes of a single species that migrated to a deep photic zone refuge during the height of PETM warming and eutrophication. Anomalously, high rates of organic matter remineralization characterized these depths during the event and led to lower saturation levels, which caused malformation. The proposed mechanism explains the co-occurrence of malformed Discoaster with pristine species that grew in the upper photic zone; moreover, it illuminates why malformation is a rare phenomenon in the paleontological record.